Peningkatan Partisipasi Siswa dalam Pendidikan Kewarganegaraan melalui Kegiatan Ice Breaking Berbasis Storytelling - Lea, Mella Angella; Wati, Ratna Kartika; Sadeli, Elly Hasan; Priyanto, Eko (Journal of Civic Education, 2025)
This study aims to describe the implementation of storytelling ice-breaking in Pancasila Education and to analyze the factors that contribute to increased student participation in Grade 8 at SMP Negeri 4 Wadaslintang. The research used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The subjects of this study were the Pancasila Education teacher and Grade 8 students. Data analysis involved collecting data, reducing data, presenting data, and drawing conclusions. The results show that the application of storytelling ice breaking creates a more engaging learning atmosphere, increases students' motivation and self-confidence, and encourages them to be more active in participating in discussions. Some challenge remained, such as limited teacher creativity and a lack of support from the learning environment. The study concludes that storytelling ice-breaking can be an effective strategy to improve student participation in Pancasila Education learning, especially when implemented in a well-planned manner and adapted to student characteristics.